Robust nitrate removal and bioenergy generation with elucidating functional microorganisms under carbon constraint in a novel multianode tidal constructed wetland coupled with microbial fuel cell. (October 2020) - Wang, Longmian; Pang, Qingqing; Zhou, Ying; Peng, Fuquan; He, Fei; Li, Weixin; Xu, Bin; Cui, Yibin; Zhu, Xiang
Graphical abstract: Highlights: Concurrent robust NH4 + –N and NO3 − –N removal occurred at low C/N ratio in TFCW-MFC. Flood and rest time, cycle index were key factors affecting NO3 − –N elimination. Enrichment of Variovorax and Azoarcus in anode occurred at 45 cm from the cathode. The high relative abundance of Azoarcus significantly facilitated NO3 − –N removal. Internal resistance was negatively influenced by the Acidovorax. Abstract: This study investigated synthetic wastewater treatment under low inflow C/N ratio and characterized NO3 − –N-transforming and electricity-producing bacteria in a multi-anode tidal constructed wetland–microbial fuel cell (TFCW–MFC). The optimal concurrent average removal rates of NH4 + –N and NO3 − –N were 73% and 78%, respectively, under a flood/rest/flood time of 4 h/2h/4h in "tide" mode accompanied by one recirculation. The lowest NO3 − –N concentration among all anodes was observed when the electrode gap was 45 cm. Similarly, the 45 cm anode exhibited selective enrichment of Variovorax and Azoarcus . Correction analysis showed that the high relative abundance of Azoarcus was crucial in enhancing NO3 − –N removal, and the internal resistance significantly decreased as the relative abundance of Acidovorax increased . These results suggest that NO3 − –N removal and bioelectricity generation can be promoted in a TFCW–MFC with limited carbon by improving the culture conditions for specific genera.